Reply to 'Gastrointestinal Stromal Tumors of Pancreas' - Challa, Sundaram (JOP. Journal of the Pancreas, 2010)
No abstract available. Image: Nizam’s Institute of Medical Sciences. Panjagutta, Hyderabad, Andhra Pradesh, India.